Responsabilidad social en la investigación con humanos - Pfeiffer, María Luisa (2012)
Social responsibility in research with human beings It seems anachronistic to keep on talking of ethics and bioethics in a globalized culture. All ethics is based on a responsibility that acknowledges the value of the other because it forces an answer and this answer is supposed to be free. The exercise of freedom improves, grows, increases when limits are part of it. The possibilities of the answer are constructed by exchange when the limits act upon the behavior of the individual. In bioethics there is a strong tendency to associate responsibility with acts of individual relation. This neglects the strictly solidary character of responsibility. Freedom is conditioned by equality but much more by solidarity. Solidarity forces us to accept limits imposed to us by coexistence. Health is the space where this becomes relevant. Therefore it is necessary to think of social responsibility from a bioethics perspective based on human rights, especially on the right to health. This work does precisely that, focusing on research with human beings.